Prolonged Response to Pembrolizumab in Spindle Cell Squamous Cell Carcinoma Metastatic to the Central Nervous System. (May 2019) - Liu, Yuxin; Fitzgerald, Bailey; Perry, Edward; Pathak, Ashutosh; Chao, Herta H.
Background. Cutaneous squamous cell carcinoma is a common type of skin cancer, with aggressive metastatic or locally advanced disease representing an uncommon minority of presentations. Emerging data have supported the Food and Drug Administration approval of the anti-PD1 human monoclonal antibody cemiplimab in select patients with advanced disease. However, there is limited data regarding durability of effect and generalizability of anti-PD1 effectiveness across therapies. Additionally, information regarding applicability of these regimens to the rare spindle cell variant and to central nervous system metastases for cutaneous squamous cell carcinoma is unfortunately limited. Case Presentation . A 72-year-old gentleman presented with facial neurological deficits and a dermal nodule and was diagnosed with spindle cell squamous cell carcinoma with perineural invasion. His course was notable for early intracranial metastasis with progressive neurological deficits despite recurrent radiation therapy with intermittent response. When progressive left-sided weakness prompted imaging evaluation that was concerning for disease recurrence after exhaustion of radiation therapy options, the patient was started on systemic therapy with the anti-PD-1 monoclonal antibody treatment prior to the approval of cemiplimab. Pembrolizumab was chosen due to the fact that the patient was ineligible for clinical trials and for its every 21-day dosing. With this treatment, he has achieved a durable clinical response, resulting in near resolution of neurological deficits and more than a year of progression-free survival to date, despite aggressive intracranial disease. Conclusions. This case suggests that anti-PD-1 therapy with pembrolizumab may represent an effective and well-tolerated treatment for patients with metastatic spindle cell squamous cell carcinoma including patients with metastatic disease to the central nervous system.